Pathological mandible fracture related to cystic lesion: clinical case report (Research, Society and Development, 2021)
Mandible fractures are often caused by direct trauma, however, pathological fractures may arise, due to tumor or cystic lesions. Pathological fractures of the mandible are defined as fractures that occur in places where bone has previously been weakened by a pathological process. The most commonly related causes are after surgical procedures to extract third molars and the presence of cystic lesions. The main sign of this type of fracture is tooth disarticulation. The aim of this study was to report a clinical case, of a female patient, 61 years old, leucoderma, who presented a dentigerous cyst of great extension associated with tooth 38 and that during the trans-operative period there was a pathological fracture. The surgical approach is determined by the type and location of the fracture in the mandible. Its etiology should also be taken into account, when related to cysts, the extension of the lesion and the amount of remaining bone should be focused, in order to consider the ideal type of reduction and fixation for each case. In cases where the healthy bone remnant is not sufficient or is separated by a large defect, resection of the involved region may be indicated, possibly accompanied by immediate or secondary reconstruction. It was concluded that reduction and fixation of mandibular fractures should occur as accurately and quickly as possible, as malocclusion is a serious long-term complication. In addition, a team prepared for this and any type of occurrence during and after maxillofacial procedures is needed.